Self‐reported history of estrogen hormone therapy differentiates rates of amyloid accumulation (PiB‐PET) relative to males: Findings from the Harvard Aging Brain Study. (December 2021) - Rubinstein, Zoe B.; Buckley, Rachel F.; Scott, Matthew R.; Manning, Lyssa K.; Mayblyum, Danielle V.; Thibault, Emma G.; Jacobs, Heidi I.L.; Farrell, Michelle E.; Properzi, Michael J.; Rabin, Jennifer S.; Chhatwal, Jasmeer P.; Lois, Cristina; et al.
Abstract: Background: Women's Health Initiative Memory Study (WHIMS) findings suggest that hormone therapy increases risk of dementia. Conversely, evidence from the Kronos Early Estrogen Prevention Study (KEEPS) implicates estrogen hormone therapy (HT) as protective against ß‐amyloid (Aß) burden. We sought to explore if self‐reported HT use is associated with rates of Aß accumulation in an observational sample of clinically‐unimpaired older adults. Method: 134 participants (Age=73yrs±5.8) underwent at least three timepoints of Pittsburgh compound‐B (PiB)‐PET scans over an average of 9.7 years. Longitudinal PiB‐PET was examined as aggregate neocortical DVR (composite reference region: whole cerebellum + eroded white matter). Concurrent with baseline PiB‐PET, female participants self‐reported if they ever took HT. Participants were thus identified as: females who never used HT (HT‐:n=36), females who have ever taken HT to any extent (HT+:n=42), and males (M:n=56). We examined the relationship between these three groups and longitudinal PiB‐PET using linear mixed models, adjusting for baseline age, and with random slopes and intercepts. Post‐hoc analyses adjusted for APOE ε4 status and examined interactions between HT and baseline PiB‐PET on change in PiB‐PET from baseline. Result: While we found no significant sex (male/female) difference in PiB‐PET accumulation (t=1.5, p >0.05, Fig 1A), we observed significant HT group differences with HT‐ exhibiting approximately half the PiB‐PET rate of change than M (t=2.3, p =0.02) and HT+ (t=1.8, p =0.07; Fig 1B). There was no significant slope difference between M and HT+ (t=0.32, p =0.75). These differences survived after covarying for APOE ε4. A three‐way interaction with baseline PiB‐PET revealed a greater slope difference between HT‐ and M (t=2.1, p =0.04) in those with higher baseline PiB‐PET relative to lower baseline PiB‐PET (Fig 2). Conclusion: HT‐ showed significantly slower rates of Aß accumulation than males and a trend‐level slower rate compared to HT+; these differences appear heightened with greater baseline Aß burden. With similar ages across HT groups (p=0.20), these differences did not appear to be a function of chronological age. It remains unclear whether the introduction of estrogen, a mediating commonality, or collider bias is driving these results. Our findings, in conjunction with other studies, suggest the relationship between HT and Aß is complicated and necessitates examination of HT type and duration.